2010
DOI: 10.1103/physrevstab.13.113501
|View full text |Cite
|
Sign up to set email alerts
|

Fast ferroelectric phase shifters for energy recovery linacs

Abstract: Fast phase shifters are described that use a novel barium strontium titanate ceramic that can rapidly change its dielectric constant as an external bias voltage is changed. These phase shifters promise to reduce by $10 times the power requirements for the rf source needed to drive an energy recovery linac (ERL). Such phase shifters will be coupled with superconducting radiofrequency cavities so as to tune them to compensate for phase instabilities, whether beam-driven or those caused by microphonics. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…[1][2][3] Recently, the accelerator applications of BST-based ferroelectrics were also reported: bulk BST ferroelectrics can be used as active elements of electrically controlled switches and phase shifters in pulse compressors or power distribution circuits of future linear colliders as well as tuning layers for the dielectric-based accelerating structures. [4][5][6][7] The main requirement for the electrical properties of ceramic materials for tunable microwave applications is a combination of relatively low dielectric constant, low loss tangents, and high dielectric tunability. 8,9 However, the high inherent material loss and high dielectric constant of pure BST has restricted its application in tunable microwave devices.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recently, the accelerator applications of BST-based ferroelectrics were also reported: bulk BST ferroelectrics can be used as active elements of electrically controlled switches and phase shifters in pulse compressors or power distribution circuits of future linear colliders as well as tuning layers for the dielectric-based accelerating structures. [4][5][6][7] The main requirement for the electrical properties of ceramic materials for tunable microwave applications is a combination of relatively low dielectric constant, low loss tangents, and high dielectric tunability. 8,9 However, the high inherent material loss and high dielectric constant of pure BST has restricted its application in tunable microwave devices.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recently, the accelerator applications of BST-based ferroelectrics were also reported. 4,5 The main requirement for the electrical properties of ceramic materials for tunable applications is a combination of relatively low dielectric constant, low loss tangents, and high dielectric tunability. 6 The high inherent materials loss and high dielectric constant of BST, however, have restricted its application in tunable devices.…”
Section: )O 3 Ceramics In the Terahertz Rangementioning
confidence: 99%
“…Ba 1− x Sr x TiO 3 (BST)‐based composites with microwave dielectrics inclusions have been attracting increasingly interest for tunable microwave device applications such as tunable oscillators, varactors, and phase shifters because of their highly electrically tunable dielectric response . Materials with low permittivity (ε), low loss tangent (tanδ), and high tunability ( tun = [ε( E 0 )−ε( E )]/ε( E 0 ), where ε( E 0 ) and ε( E ) is the zero‐field and maximum applied‐field permittivity, respectively) are essential for these applications.…”
Section: Introductionmentioning
confidence: 99%
“…B A 1ÀX SR X TIO 3 (BST)-based composites with microwave dielectrics inclusions have been attracting increasingly interest for tunable microwave device applications such as tunable oscillators, varactors, and phase shifters because of their highly electrically tunable dielectric response. [1][2][3][4][5] Materials with low permittivity (e), low loss tangent (tand), and high tunability (tun = [e(E 0 )Àe(E)]/e(E 0 ), where e(E 0 ) and e(E) is the zero-field and maximum applied-field permittivity, respectively) are essential for these applications. Nenasheva et al found that the increase in concentration of Mg 2 TiO 4 in compositions BST-Mg 2 TiO 4 + MgO led to a decrease in the permittivity of the mixture and the increase in its tunability by a DC field.…”
Section: Introductionmentioning
confidence: 99%